IMPROVEMENT OF THE LICENSING SERVICES MECHANISM AT THE ONE-STOP INVESTMENT AND INTEGRATED SERVICE OFFICE USING SOFT SYSTEM METHODOLOGY - Subowo, Eko; Maarif, M Syamsul; Arkeman, Yandra; Kirbrandoko, Kirbrandoko (Jurnal Aplikasi Manajemen, 2019)
This study geared to analyze current problems faced by the One Stop Investment and Integrated Services Offices (Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu/DPMPTSP) in delivering licenses to private sectors and subsequently to construct conceptual models in improving their performance. Respondents of this study are experts and leaders representing Ministries/Institutions, DPMPTSP, Technical Offices, Local Governments, and business actors, which total up to 36 respondents. The data were analyzed through Soft System Methodology (SSM) techniques. The results showed that the improvement of licensing service mechanism is the most relevant effort to support the realization of an integrated investment licensing service. Improved licensing service mechanisms are expected to be able to create more effective and efficient licensing services in terms of time, process, and requirements that have been expected by business actors. Through the application of seven stages of SSM analysis, two action plans for improvement are proposed, namely the improvement of the Online Single Submission (OSS) system and Institutional Improvement. Further research is needed to study the implication of time and cost saving could be made if the new models were implemented.